THE INFLUENCE OF SPIRITUAL INTELLIGENCE ON COPING EFFORTS: THE MEDIATING ROLE OF COGNITIVE APPRAISAL AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kun Ika Nur Rahayu; Chatarina Umbul Wahyuni; Mochammad Bagus Qomaruddin; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2026)
Diabetes mellitus requires lifelong treatment and imposes persistent psychological stress on patients. Spiritual intelligence (has been recognized as a psychological resource that promotes resilience and adaptation; however, the role of cognitive appraisal as a mechanism linking spiritual intelligence to coping remains unclear. This study aimed to examine the mediating role of cognitive appraisal in the relationship between spiritual intelligence and coping among patients with type 2 diabetes mellitus. A cross-sectional study was conducted among 300 patients with type 2 diabetes mellitus aged 30–50 years in Kediri, Indonesia. Data were collected using the Spiritual Intelligence Self-Report Inventory (SISRI-24), the Primary Appraisal Secondary Appraisal (PASA) scale, and the Brief COPE questionnaire. Path analysis with bootstrapping was performed to examine the mediating role of cognitive appraisal. Spiritual intelligence significantly predicted cognitive appraisal (β = 0.819, p < 0.001) and coping (β = 0.335, p < 0.001). Cognitive appraisal also positively predicted coping (β = 0.425, p < 0.001) and partially mediated the relationship between spiritual intelligence and coping, accounting for 40.28% of the total effect. The model explained 31.7% of the variance in cognitive appraisal and 45.3% of the variance in coping. These findings suggest that interventions integrating spiritual intelligence and psychological dimensions by enhancing spiritual intelligence and strengthening cognitive appraisal may improve coping capacity, treatment adherence, and long-term self-management among patients with type 2 diabetes mellitus. Future longitudinal studies are recommended to establish causal relationships and investigate demographic and clinical factors that may moderate these associations.